On the Stability of Alternative Additive Equations in Multi-β-Normed Spaces. (1st August 2016) - Yang, Xiuzhong; Ma, Jing; Liu, Guofen
Abstract : We introduce the notion of multi-β -normed space (0 < β ≤ 1 ) and study the stability of the alternative additive functional equation of two forms in this type of space.